Ayurvedic management of Karshya – A Case Report. - Reena Kulkarni; Pritesh Premchand Nahar (Journal of Ayurveda and Holistic Medicine (JAHM), 2026)
Introduction: Apatarpanajanya Vyadhi (disorder arising from inadequate nourishment) with Krushatva (undernutrition) is termed as Karshya, comparable to underweight. Underweight prevalence though decreased to 32.1% (National Family Health Survey - 5), still remains. Despite several national nutritional programmes, undernutrition remains a significant health challenge in children. Ashwagandhadi Leha is indicated in Karshya for its Balya (strength promoting), Brimhana (nourishing) and Rasayana (rejuvenating) properties. Limitation with administration of Ghrita and Leha yogas in children is due to non-acceptance resulting from bitter taste, smell or texture. In such conditions, a modified pharmaceutically granules formulation Ashwagandhadi leha granules (ALG) could be a choice of intervention. Materials and methods: A single case of Karshya was treated and documented for changes in clinical manifestation of Karshya, improvement in anthropometric parameters height, weight, mid upper arm circumference (MUAC), head circumference, chest circumference, skin fold thickness, Body mass index (BMI) and WHO Z Score for height-for-weight at baseline, on 90th day and at follow-up. Haematological parameters, serum protein, serum albumin, serum lipids, urine routine and microscopic were assessed at baseline and on 90th day. Results: Upon completion of intervention, improvements in weight (1.5kg), height (6cm), BMI (1.1 kg/m2), MUAC (2.5cm) and other anthropometric parameters were noted. However, there was no significant change in haematological and serological parameters. The results can be attributed to the Brimhana effect intervention supporting overall nutritional improvement. Conclusion: ALG is a safe, palatable and nutritionally rich Ayurvedic formulation with Balya, Brimhana and Rasayana properties that improves nutritional status and anthropometric parameters in undernutrition. However, this being a single case study, further evaluation of ALG in large sample and if possible controlled studies can generate substantial evidence and may serve as an effective dietary therapeutic intervention. During the course of treatment there were no adverse drug reactions (ADR) indicating the intervention was safe and effective.